Desenvolvimento da produção agrícola e intervenção social: estudo de caso em uma comunidade da Reserva de Desenvolvimento Sustentável de Mamirauá - NASCIMENTO, Ana Claudeise Silva do (Universidade Federal do Pará, 2012)
This work is the result of an ethnographic study in a small riverside community of the Amazon flooded area, emphasizing its particularities in relation to the use of natural resources. The subject of the analysis was a smallholder agricultural project, which was developed by implementing the results of scientific research on the participatory management of natural resources. Technicians from Mamirauá Institute and the peasants met periodically to evaluate the project’s processes and results. This study contributes to the understanding of the impacts of investments in agriculture, enabling an interaction between processes of reflection and action. The main objective of this dissertation is to assess a situation of social intervention directed at the sustained management of agricultural produce in a protected area of flooded forest (Sustainable Development Reserve). This study has indicators which contribute to the understanding of the impacts of investments in agriculture in a small community called São Francisco do Aiucá, enabling interaction between intention/implementation based on the understanding of the results and the evaluation of the social intervention. Using some indicators, built through the use of participatory methodologies, it was possible to analyze changes in the economic activities of São Francisco do Aiucá, and other forms of natural resources use, identifying ways to both diversify the crops and undertake new alternatives for the commercialization of the produce.